Port-site metastasis as a primary complication following diagnostic laparoscopy of fallopian tube carcinoma: A case report. Issue 26 (June 2018) - Chen, Yan; Ling, Chen; Bian, Ce
Abstract: Rationale: Fallopian tube carcinoma is a rare female genital cancer with no specific clinical and surgical features. It is hardly diagnosed on imaging due to non-specific presentation. Laparoscopy has been recommended as the diagnostic procedure for the assessment of suspicious ovarian and adnexal masses. However, it has brought new complications like tumor recurrences at the trocar insertion sites, called port-site metastasis (PSM). Patient concerns: A 65-year-old, postmenopausal woman presented to hospital with loss of appetite, Ultrasound showed ill-defined pelvic mass. The patient was diagnosed with fallopian tube carcinoma by a diagnostic laparoscopy. Diagnoses: The PSM as a primary complication following diagnostic laparoscopy of fallopian tube carcinoma, which is presumed by positron emission tomography/computed tomography and confirmed by Nodule resection and further pathological assessment. Interventions: As port-site metastasis was suspected, the patient was advised to undergo umbilical mass resection. Outcomes: the patient has no signs of recurrence was detected 20 months after the last surgery during follow-up. Lessions: Laparoscopy plays a significant role in the diagnose and treatment of fallopian tubal and ovarian malignancies but has a risk of PSM occurrence. When isolated PSM occurs the management should be local resection.